THE EFFECT OF SOLUTION HEAT TREATMENT HOLDING TIME VARIATIONS ON THE MECHANICAL PROPERTIES OF ALUMINUM A-6061 BY THE TIG WELDING PROCESS - Azwinur, Azwinur (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
Aluminum and its alloys are metals that are widely used in the engineering field because its have advantages including good formability, relatively high tensile strength, corrosion resistance and a welding process for the joints. General structure, structures that have poor mechanical properties. To overcome this problem, the material that has been welded is heat treated or heat treated according to temperature and time management) which is suitable in addition to good mechanical properties as well as to reduce residual stresses. The purpose of this research is to determine the tensile strength and hardness value of welding joints of Aluminum 6061 with a variation of Holding Time 1, 2, 3 hours in the Solution Heat Treatment process with a temperature of 5000C. The results showed that based on the results of the tensile test, it showed that the holding time affected the value of the tensile strength and strain of the welding joint where the highest tensile test value was at a holding time of 1 hour, while the highest strain value was at a holding time of 2 hours. Then from the hardness test data, it shows that the heating duration or holding time affects the hardness value of the material both in the weld metal, HAZ, and base metal areas. In the weld metal area, the highest hardness value is at a holding time of 3 hours. The HAZ area has the highest hardness value at a holding time of 2 hours, while the base metal region has the highest hardness value at a holding time of 1 hour.